Exploring the Role of Education in Social Status - Gharini Rahmadhani; Tri Rini Widiarti; Dr., Djoko Sutrisno, S.Pd., M.Pd. (Global Synthesis in Education Journal, 2024)
This research explores the multifaceted role of education in shaping social status within communities. Education, as defined by various scholars, serves as a conscious effort to prepare individuals for their future roles, fostering cultural values, and promoting social, political, and economic development. The societal changes brought about by rapid developments lead to both progress and challenges, requiring a thoughtful examination of education's role. The methodology employs library research, specifically a qualitative descriptive approach, to analyze written sources such as books, papers, and articles. The research focuses on methods determining social strata and delves into the impact of education on social class formation, considering accessibility, roles, and economic implications. Results highlight education's significance in individual growth, societal progress, and community welfare. Definitions of education vary, emphasizing combating ignorance, transmitting cultural values, and fostering self-development. Social class, acting as an obstacle to meeting basic needs, intertwines with education as a social institution influencing socialization and cultural continuity. The relationship between education and social stratification is complex, influencing individuals' positions based on accessibility, social networks, and economic opportunities. The research acknowledges the dynamic nature of social stratification, where open societies provide opportunities for upward mobility. It also discusses methods to determine social groups and underscores the varied outcomes based on the chosen method. The research concludes by emphasizing the profound impact of education on social status. It serves as a catalyst for intellectual development, creates social networks, and influences economic opportunities. Acknowledging education's transformative role, the study advocates for equitable access to education to reduce social disparities and build a more inclusive society.